Clinical characteristics and outcomes of non-tuberculous mycobacterial pulmonary infections after hematopoietic stem cell transplantation: A retrospective cohort study - Zahia Esber; Hamza Salam; Shefali Godara; Ayman Soubani (Hematology, Transfusion and Cell Therapy)
Introduction: Non-tuberculous mycobacterial infections are rising as complications of bone marrow transplantation with lung disease being the most common clinical presentation. The identification and management of these infections in hematopoietic stem cell transplantation patients remains underrecognized. This study aims to investigate the clinical characteristics and outcomes in patients with post-transplant pulmonary infections. Methods: The charts of 3,000 adult patients who received transplants over 11 years at the Karmanos Cancer Institute, a tertiary-care cancer center in Detroit, were reviewed. The diagnoses of post-transplant pulmonary non-tuberculous mycobacterial infections of 51 patients were defined as definite, probable or possible based on the American Thoracic Society (ATS) and Centers for Disease Control and Prevention guidelines. The identified organisms were further characterized as rapid- or slow-growing mycobacteria. Clinical characteristics, risk factors, microbiologic data, therapy and outcomes of the patients were collected and analyzed. Results: About half (n = 26; 51%) of the patients were identified with definite pulmonary infection. There was a trend of cardiovascular and pulmonary comorbidities in these patients. The majority (n = 44; 86.3%) were on steroid and immunosuppressive therapy in the setting of graft-versus-host disease. The most common presenting symptoms were a combination of change in cough and worsening shortness of breath. The most common radiologic pattern was nodular infiltrates in 15 (29.4%) patients. Mycobacterium avium complex was identified in 38 (74.5%) patients. The majority of patients with these infections (76.5%) did not receive antimycobacterial therapy. Survival was reported in 42 (82.4%) patients. Conclusion: Outcomes vary significantly among non-tuberculous mycobacterial pulmonary infections based on mycobacterial species, rate of colonization and degree of immunosuppression. The prognosis is overall good due to slow growing mycobacteria. Prospective multicenter studies are required to further guide the management of these patients.